A REVIEW ON THE ROLES OF AI AND MACHINE LEARNING IN OPTIMIZING RESOURCE ALLOCATION, FORECASTING WORKLOAD DEMANDS, AND ENHANCING SECURITY MEASURES IN THE CLOUD - RASHID, AIDA MARYANI (Journal of Engineering & Technological Advances, 2024)
The symbiotic link between artificial intelligence (AI) and cloud computing emerges as a revolutionary force in the continuously evolving world of digital infrastructure. This paper intends to highlight the complicated roles that artificial intelligence (AI) and machine learning have played in reshaping the landscape of cloud computing. In particular, the inquiry tackles three essential areas: cloud resource allocation optimization, workload demand forecast accuracy, and security measure fortification. A fundamental problem as businesses move more and more toward cloud systems is the dynamic resource allocation to manage changing workloads. Underutilization and overutilization lead to inefficiencies that are detrimental for both overall performance and cost-effectiveness.